Women, work, and economic growth : leveling the playing field - Kochhar, Kalpana; Jain-Chandra, Sonali, 1975-; Newiak, Monique (International Monetary Fund, 2017)
Women make up a little over half of the world's population, but their contribution to measured economic activity and growth is far below its potential. Despite significant progress in recent decades, labor markets across the world remain divided along gender lines, and progress toward gender equality seems to have stalled. The challenges of growth, job creation, and inclusion are closely intertwined. This volume brings together key research by IMF economists on issues related to gender and macroeconomics. In addition to providing policy prescriptions and case studies from IMF member countries, the chapters also look at the gender gap from an economic point of view.